In search of best impact factor and citation indexed journals towards achieving the goals of universities - Jusoff, Kamaruzaman (2008)
This paper provides an introduction to the concept and importance of journal impact factor (JIF), citation indexes. The paper takes the form of a short history of JIF, the importance of journal performance indicators, about calculating and determining JIF and the significance of using Citation Indexes. Elements of the factors affecting impact factor namely scientometrics and journalology were also highlighted. A guide to locating the best impact factor journals in various research fields was demonstrated. Despite that JIF is still a dilemma for some fields of research, academic members are still subjected to the Key Performance Index (KPI) criteria compliance for further promotion and excellence service awards on top of the need to generate high impact research publications.